The labyrinth and the wasteland : Spatial coordinates of the German image in nineteenth-century Russian literature - Walker, Joshua S. (Trinity College (Dublin, Ireland). Department of Russian & Slavonic Studies, 2011)
An analysis of the literary stereotypes of Germans in 19th century Russian literature with specific attention to how these images describe Russia in spatial terms and construct Russian identity. Considering the prevalence of German literary characters in the works of Aleksandr Pushkin, Nikolai Gogol, Ivan Turgenev, Fyodor Dostoevsky, and Anton Chekhov, the scarcity of scholarly literature on the topic is striking. Many of these characters present a puzzle, because their "Germanness" does not appear to bear upon the action of the story, especially in the work of Chekhov and Turgenev. According to one of the few scholars to take on the problem, the presence of these characters "... was usually meant to provide comic relief (as in Pushkin's 'The Undertaker' or Gogol's 'Nevsky Prospect'), supply fodder for parody (cf. Hermann in pushkin's Queen of Spades), or give impetus to moralistic diatribes (as is often the case in Gogol) [Diament, Goncharov's Oblomov, p.29]. My thesis challenges this received assumption with an analysis of the deep structures of the interaction between the Russian and German characters. I aim to demonstrate that the role of the Germans in Russian literature goes beyond what the above scholar implies, because the depiction of Germans constructs and modifies the Self Image of Russian identity. This is effected by casting the Russian as open, free, unpredictable, vital, simple, youthful, abstract, spiritual, and disorderly, as opposed to the German, who is constricted, restricted, rational, dull, condescending, elderly, explicit, material, and orderly. Given the hybrid and synthetic nature of the Russian-German interaction through history, and considering the prevalence of Germans within the Russian Empire, I argue that the literary German can function both as an external foreign Other, and also as an internal aspect of Russianness. Two competing visions of Russia and Russianness vis-a-vis the German thus emerged in the mid-19th century - as Mutually Exclusive and as Synthetic. The depiction of Gennans in Russian literature thus depends upon which of these two lenses a given writer chooses to deploy.
Keywords: Russian and Slavonic Studies, Ph.D.; Ph.D. Trinity College Dublin